The appropriateness of more intensive colonoscopy screening than recommended in medicare beneficiaries: A modeling study - Van Hees, F.; Zauber, A.; Klabunde, C.; Goede, S.; Lansdorp_Vogelaar, Iris; Van Ballegooijen, M. (2014)
Importance: Many Medicare beneficiaries undergo more intensive colonoscopy screening than recommended. Whether this is favorable for beneficiaries and efficient from a societal perspective is uncertain.Objective: To determine whether more intensive colonoscopy screening than recommended is favorable for Medicare beneficiaries (ie, whether it results in a net health benefit) and whether it is efficient from a societal perspective (ie, whether the net health benefit justifies the additional resources required).Design, Setting, and Participants: Microsimulation modeling study of 65-year-old Medicare beneficiaries at average risk for colorectal cancer (CRC) and with an average life expectancy who underwent a screening colonoscopy at 55 years with negative results.Interventions: Colonoscopy screening as recommended by guidelines (ie, at 65 and 75 years) vs scenarios with a shorter screening interval (5 or 3 instead of 10 years) or in which screening was continued to 85 or 95 years.Main Outcomes and Measures: Quality-adjusted life-years (QALYs) gained (measure of net health benefit); additional colonoscopies required per additional QALY gained and additional costs per additional QALY gained (measures of efficiency).Results: Screening previously screened Medicare beneficiaries more intensively than recommended resulted in only small increases in CRC deaths prevented and life-years gained. In comparison, the increases in colonoscopies performed and colonoscopy-related complications experienced were large. As a result, all scenarios of more intensive screening than recommended resulted in a loss of QALYs, rather than a gain (ie, a net harm). The only exception was shortening the screening interval from 10 to 5 years, which resulted in 0.7 QALYs gained per 1000 beneficiaries. However, this scenario was inefficient because it required no less than 909 additional colonoscopies and an additional $711 000 per additional QALY gained. Results in previously unscreened beneficiaries were slightly less unfavorable, but conclusions were identical.Conclusions and Relevance: Screening Medicare beneficiaries more intensively than recommended is not only inefficient from a societal perspective; often it is also unfavorable for those being screened. This study provides evidence and a clear rationale for clinicians and policy makers to actively discourage this practice.